Factors Associated with Comfort after Liver Resection among Patients with Hepatocellular Carcinoma - Yaxi Huang; Chutima Chantamit-o-Pas; Wipa Wiseso (Korean Journal of Adult Nursing, 2026)
Purpose: Guided by Kolcaba’s Comfort Theory, this study aimed to identify predictors of comfort among patients with hepatocellular carcinoma after liver resection. Methods: This cross-sectional predictive correlational study included 132 patients with hepatocellular carcinoma who underwent liver resection in Wenzhou, China. Demographic and clinical characteristics, including age, were collected. Comfort, pain severity, pain interference, perceived social support, and early mobilization were assessed using validated instruments. Data were analyzed using descriptive statistics, the independent-samples t-test, one-way analysis of variance, Pearson correlation coefficients, and standard multiple linear regression. Results: Participants reported a moderate overall level of comfort. In the multiple regression model, pain interference (β=−.25, p=.008) and perceived social support (β=.39, p